1999
DOI: 10.1080/00050069908257427
|View full text |Cite
|
Sign up to set email alerts
|

Death penalty attitudes and juror decisions in australia

Abstract: Although Australia does not currently have a death penalty law, an increasing concern about violent crime has raised the possibility that capital punishment, abolished in the 1960s, may be reconsidered. to determine the death penalty attitudes and potential jury behaviour of younger Australians, who have grown up without capital punishment, an experiment was conducted with 166 Australians, aged 18 to 30 years. Jurors who professed anti‐(29%) or pro‐ (71%) death penalty attitudes were exposed to one of four mur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 12 publications
1
10
0
Order By: Relevance
“…Given the higher sentences for those within the VIS condition, we expected that future dangerousness ratings should also be higher for this condition than in the non-VIS condition, as sentences are often correlated with ''dangerousness'' ratings (ForsterLee et al, 1999;Gottfredson, Gottfredson, & Conly, 1989;Sanderson, Zanna, & Darley, 2000). We predicted that both male and female jurors should give the highest ratings to female offenders, indicating their violent acts are considered deviant behaviour.…”
Section: Overview Of the Present Studymentioning
confidence: 98%
See 2 more Smart Citations
“…Given the higher sentences for those within the VIS condition, we expected that future dangerousness ratings should also be higher for this condition than in the non-VIS condition, as sentences are often correlated with ''dangerousness'' ratings (ForsterLee et al, 1999;Gottfredson, Gottfredson, & Conly, 1989;Sanderson, Zanna, & Darley, 2000). We predicted that both male and female jurors should give the highest ratings to female offenders, indicating their violent acts are considered deviant behaviour.…”
Section: Overview Of the Present Studymentioning
confidence: 98%
“…In the first instance Australian audiences, and those of other western countries, are familiar with the American justice system, particularly through popular television programming. Subsequently, this methodology has demonstrated its worth for collecting information on community attitudes regarding both actual and proposed innovations in the criminal justice system (ForsterLee, Horowitz, ForsterLee, King, & Ronlund, 1999;Hills & Thomson, 1999). Perhaps more important is the fact that jurors already make sentencing decisions in the US and Australia often follows American trends across issues as diverse as war, economics and taxation (Hillman, 2003;Lahgue, 2003;Lusty, 2003;Waters, 1999).…”
Section: Overview Of the Present Studymentioning
confidence: 99%
See 1 more Smart Citation
“…The transcript of the case, based on an actual criminal trial, was modified by ForsterLee, Horowitz, Forsterlee, King, and Ronlund (1999), and rewritten to fit an Australian legal context. A lawyer and a judge reviewed the prosecution and defense summations, while the lengthy judicial instructions were rewritten by a Queensland barrister and reviewed by a magistrate.…”
Section: Trial Materialsmentioning
confidence: 99%
“…Thus, an immigrant offender can be expected to benefit from a more lenient judgment if he adopts French culture than if he does not. However, the characteristics of the offender are not the only factors involved when making a judgment; the characteristics of the person making the judgment, particularly regarding their ideological orientation, also play a role (Fosterlee, Horowitz, Fosterlee, King & Ronlund, 1999). Thus, Mahfud, Badea and N'Gbala (2015) found that ideological orientation influenced the perception of cultural distance with the immigrant, involving a greater or lesser degree of prejudice.…”
Section: Ethnicity and Acculturation Strategiesmentioning
confidence: 99%